'Modernity' and the Making of Social Order in Twentieth-Century Europe. (2nd April 2014) - SWEENEY, DENNIS
<x content-type="archive" xml:space="preserve">Abstract</x> It is hard not to be struck by the continuing interest in the concept of 'modernity' or 'the modern' for making sense of the economic, cultural and political transformations of twentieth-century Europe. Seemingly laid to rest by the early 1980s for its association with modernisation theory, modernity as a concept was revived during the late 1980s and 1990s largely by European historians working on countries, especially Germany and Russia, with nineteenth- and twentieth-century histories that modernisation theorists deemed models of developmental backwardness or case studies in the failure to modernise and its consequences. But, like its striking re-appearance in scholarship on those areas of the world – especially Asia and Africa – written off as the most irredeemably un-modern or 'traditional' by modernisation theorists, this renewed interest in modernity derives from very different interventions in post-structuralist theory and cultural and postcolonial studies, which have generated new definitions, and critiques 'modernity' and its 'dark side' from the vantage point of 'postmodernity'.